ANALISIS MUTU KIMIA DAN ORGANOLEPTIK PUPUK ORGANIK TANDAN KOSONG KELAPA SAWIT DENGAN DOSIS EM-4 BERBEDA - Ade Maya Mustika; Penti Suryani; Tahrir Aulawi (Jurnal Agroteknologi, 2019)
This research was conducted from August to December 2016 at the PEM Laboratory of the Faculty of Agriculture and Animal Sciences State Islamic University of Sultan Syarif Kasim Riau and Central Plantation Service Laboratory. The study aims to 1). Analyzing the chemical and organoleptic qualites of Oil Palm Empty Bunches organic fertilizer with the addition of different EM-4 doses 2). Determine the best quality on the quality of Oil Palm Empty Bunches organic fertilizer. The experimental design was Completely Randomized Design (CRD) and three replications. The treatment were application of (EM4) consist of 0 ml, 5 ml, 10 ml, 15 ml, 20 ml, and 25 ml. Results analysis using ANOVA variance, simple linear regression and validity and reliability analysis. The results showed that the addition of EM-4 resulted in quality in accordance with SNI 19-7030-2004 with the dose of 5 ml, 10 ml, and 15 ml, respectively, but on the measurement of fertilizer pH organic Oil Palm Empty Bunches does not meet SNI: 19-7030-2004.